1990
DOI: 10.1111/j.1399-302x.1990.tb00437.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of pH in salivary histidine‐rich polypeptide antifungal germ tube inhibitory activity

Abstract: Purified synthetic salivary histidine-rich polypeptides (HRPs) 2, 3, 4, 5 and 6 were found to inhibit Candida albicans conversion of blastospores to germ tubes. HRP-4 was the best inhibitor within the pH 5 to 7 range tested and all of the HRPs were observed to lose potency as the pH was raised from 5 to 7. The pH pattern obtained with a synthetic homologous histidine peptide suggested that the protonated form of the histidine imidazole residues of the HRPs was important to the germ tube antifungal activity. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Previous reports have shown that saliva has antifungal properties, mediated through histidine-rich polypeptides (HRPs) [31][32][33]. In these reports, however, inhibitory effects of whole saliva were observed following acidification and/or boiling of the saliva, which is thought to release HRPs from salivary protein complexes or inactivate inhibitors of HRPs in saliva.…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports have shown that saliva has antifungal properties, mediated through histidine-rich polypeptides (HRPs) [31][32][33]. In these reports, however, inhibitory effects of whole saliva were observed following acidification and/or boiling of the saliva, which is thought to release HRPs from salivary protein complexes or inactivate inhibitors of HRPs in saliva.…”
Section: Discussionmentioning
confidence: 94%
“…Histatins also have anti-fungal properties and appear to constitute a non-immune protection system for the oral surfaces. They are fungicidal to Candida albicans [34] with histatin 5 being the most active [35] whilst histatin 4 inhibits blastospore germination [36,371. Saliva has also been reported to inhibit the infectivity of human immunodeficiency virus (HIV-1) [37] and, whilst histatins do not exhibit broad spectrum anti-viral activity, a possible involvement cannot be excluded [ 3 11.…”
Section: Histidine-rich Proteinsmentioning
confidence: 99%
“…The anti-candidal activities of individual histatins were compared with each other at the levels of the killing of blastospores and germinated cells and the inhibition of germination (Xu et al, 1991;Santarpia et al, 1990; see below). Moreover, the investigators evaluated the anti-candidal (blastosporicidal) activity of histatins, taking into consideration the different conditions known to occur in the oral cavity, such as pH, ionic strength, species of ions, growth phase of C. albicans, and cell number of C. albicans (Xu et al, 1991;Santarpia et al, 1990;Brant et al, 1990).…”
Section: (I) Introductionmentioning
confidence: 99%
“…However, the study did not test the effect of pH on histatin blastosporicidal activity under growth conditions. The ability of histatins to inhibit the conversion of C. albicans from the yeast form to the germinated form was dependent on pH; histatins were more effective at pH 5 than pH 7 (Brant et al, 1990). The pH of saliva ranges from 5 to 8.…”
Section: (I) Introductionmentioning
confidence: 99%
See 1 more Smart Citation